Dietary intake, physical activity and body mass index among postmenopausal women - Chaya Ranasinghe; Pallavi G Shettigar; Meenakshi Garg (Wolters Kluwer Medknow Publications, 2017)
Context: Nutrition plays a vital role in the quality of life in postmenopausal women. Aim: The aim is to determine the dietary intake, physical activity, and assess the body mass index (BMI) among postmenopausal women. Settings and Design: A community-based sample survey. Materials and Methods: The present study included 140 postmenopausal women (40-70 years) from Udupi, Manipal areas of Karnataka. The study was carried out between July and December 2013. Sociodemographic data were collected using a questionnaire. Anthropometric data included height, weight, waist, and hip circumference. Dietary intake was determined using 24 h dietary recall. Physical activity information was collected. Statistical Analysis Used: Data were analyzed using SPSS version 16 software. Paired t-test was performed to determine the dietary adequacy. Results: Obesity was 42.1% among the study participants. Increased WHR and waist circumference were 82.1% and 77.1%. Mean daily intake of calcium and saturated fatty acids were significantly higher than recommended dietary allowance (RDA) (P < 0.001). Mean intake of energy, protein, carbohydrate, mono and poly unsaturated fatty acid, fiber and sodium were significantly lower than RDA (P < 0.001). Average daily intake of cereals, pulses, roots and tubers, meat and products, fats and oils, green leafy, and other vegetables were significantly (P < 0.001) lower than RDA. Intake of fruits, milk and milk products, and sugar was significantly higher (P < 0.001) than RDA. Only 37.1% of women performed moderate or active exercises regularly. Conclusions: Even though, nutrient and food group deficiencies were observed among postmenopausal women physical inactivity and effects of menopausal transition instigate increased BMI imposing a need to educate on nutrition and physical activity.